Komparasi Manajemen Pendidikan dan Manajemen Pendidikan Islam : Suatu Tinjauan Pustaka - Siti Hadiyanti Dini Islamiati; Fatkhuri Wahmad (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Management can be applied to educational institutions. Educational institutions that want quality in their output, need good management. This research tries to compare education management with Islamic education management. The method used is a qualitative method, with data collection techniques in the form of documentation. The results of this study are that management of Islamic education is loaded with Islamic values, more complete than conventional management of education. Keywords: Management, Education, Islam